Merancang Bisnis Sampo Alami dari Ekstrak Buah Parijoto melalui Analisis Pasar - Khairani, Dianrina Fatiha; Ashari, Salsabila Zahra; Rahmawati, Rintan; Kurniawati, Marlina; Azizah, Novita Khusna; Kusuma, Ailsa Seca; Setiawati, Indah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The use of synthetic products often causes skin problems such as irritation, itching, allergies and erythema. This causes the use of natural products to become an alternative for dealing with hair problems. In entering the natural cosmetics business, market analysis is required. This research aims to analyze the market so that it can determine consumer interest and market opportunities for natural shampoo from parijoto fruit extract. Market opportunity analysis was carried out using the PAM TAM SAM SOM method, Google Trends analysis, competitor analysis, and descriptive analysis of survey results of 52 potential consumers via Google Form. The results of the analysis show that the product has a very large and profitable opportunity in the market, is superior to several competitors, and the dry/powder form of shampoo is more popular than the liquid shampoo form, 82.7% of respondents are interested in using powder shampoo and 96.2% are interested use natural shampoo.